¿Representar la explotación sexual?. La víctima puesta en escena - Laínez , Nicolás (Revista de Antropología Social, 2009)
The aim of this article is to analyze the victimizing and very emotional representations of the childrens who are sold to be prostituted in the Southeast Asia framework. The social construction of this phenomenon since the early 90´s is the result of a designed strategy by the development actors who were commited in the struggle against what they had seen like a “intolerable plague”. The victim representation stressed the innocence and the injustice inherent in that tragedy. It also put in the stage the corporal suffering and the cultural differences. This representation take part in the mercy politic, that Luc Boltanski defined as the observation trough the distance of an unlucky person by an observer. In this tandem is added a third agent, benefactor or tyrant, whose role is to increase the outrage and the s ubsequent appeal to the observer´s commitment. These representations are partially trustworthy, the reality of the victim´s life don´t seems to be always so ridiculous and one-dimensioned.
Keywords: Prostitution; Children´s prostitution; People trafficking; Representations; Victim; Body; ONG; Southeast Asia